Bland-White-Garland Syndrome in a Middle Aged Patient - A Case Report & Review of Literature - Taimur, Syed Dawood Md; Haq, M Maksumul; Khan, Saidur Rahman; Nasreen, Shahela; Qumruzzaman, KH (University Heart Journal, 2011)
Bland-White-Garland syndrome (anomalous origin of left coronary artery from the pulmonary artery) is a very rare congenital anomaly, reported in less than 0.5% of all the congenital heart disease which may result myocardial infarction, congestive heart failure and sometimes death during the early infantile period. We report a case with this anomaly, a 27 year old young lady, mother of one child presented with progressive dyspnea and cardiomagaly on X-ray. The diagnosis was made on noninvasive imaging procedure. This lady is now on optimal medications and follow up. Key words: Bland-White-Garland (BWG) syndrome; Left coronary artery (LCA); Pulmonary artery (PA). DOI: 10.3329/uhj.v6i2.7257 University Heart Journal Vol. 6, No. 2, July 2010 pp.107-109